Social Media and Planned Behaviour: Impact on TikTok Purchase Intentions - Patricy, Aklin Nindya; Dewi, Citra Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2025)
Social media nowadays significantly affects consumer buying habits, especially in the beauty sector. As a developing social commerce network, TikTok presents chances for companies like Wardah to increase sales and visibility. In order to impact online purchase intention using the Theory of Planned Behavior, this emphasizes the necessity of planned social media marketing that incorporates influencer credibility, platform utilization, and marketing content. Users of TikTok in Indonesia who had seen advertisements for Wardah participated in a quantitative survey. Partial least squares (PLS) and structural equation modeling (SEM) were used to examine the data. The findings show that purchase intention is positively impacted by marketing on social media, highlighting the significance of user interaction, reliable influencers, and focused tactics for Wardah's TikTok expansion.